The effect of coaching support behavior on the intrinsic motivation of athletes: The mediating role of psychological needs - Wang, Tongling (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The purpose of this study is to examine the effect of coaches' supporting conduct on the psychological motivation of athletes. Using the coach self-support scale, the basic psychological needs scale, and the athlete psychological fatigue questionnaire, 450 athletes were surveyed to investigate the effect of coaches' self-support on athletes' mental fatigue and the mediating role of athletes' basic psychological needs. The study indicated that the predictive effect of a sense of autonomy is weaker than that of competence and a sense of belonging when it comes to the perception of autonomous support. Although self-determination theory asserts that self-satisfaction is the most important of the three basic psychological needs, it has a moderating effect on competency and sense of belonging, and the content of choice and self-decision contained in the sense of autonomy, which includes democratic behavior and positive feedback in coaching autonomous support, has a natural consistency. Basic psychological needs partially mediate between coaching autonomy support and intrinsic drive. Among the three fundamental psychological demands, belonging has the greatest effect on internal motivation, followed by competence; autonomy has no significant effect.